Comparative studies on the modes of action of the antirhinovirus agents Ro 09-0410, Ro 09-0179, RMI-15,731, 4',6-dichloroflavan, and enviroxime. - Ninomiya, Y (1985)
Modes of action of five antirhinovirus agents were compared. Ro 09-0410, 4',6-dichloroflavan, and RMI-15,731 were active preferentially against human rhinovirus. Serotypes of the virus varied in their susceptibility to these three agents, whereas Ro 09-0179 and enviroxime showed activity against all the serotypes of the virus tested to date. Ro 09-0410, RMI-15,731, and 4',6-dichloroflavan inactivated the virus directly, although 4',6-dichloroflavan did so only slightly. Inactivation by 4',6-dichloroflavan and RMI-15,731 was associated with the binding of the agents to the virus, since the infectivity, reduced by exposure to the agents, was restored to the original level by extraction of the agents with chloroform. The binding of [3H]Ro 09-0410 to human rhinovirus type 2 was inhibited by unlabeled Ro 09-0410, 4',6-dichloroflavan, and RMI-15,731 but not by Ro 09-0179 or enviroxime. Furthermore, subtypes resistant to both 4',6-dichloroflavan and RMI-15,731 showed cross-resistance to Ro 09-0410 and vice versa. On the other hand, sublines resistant to these three agents were not cross-resistant to Ro 09-0179 or enviroxime. These results indicate (i) that Ro 09-0410, 4',6-dichloroflavan, and RMI-15,731 exert their activities through the same mode of action, namely, binding to or interaction with some specific site on the viral capsid protein, and (ii) that the binding or interaction sites for these three agents are either the same or very close to each other.